Traditional subjectivities : the Old English poetics of mentality - Mize, Britt (Toronto Anglo-Saxon series, 2013)
Mize synthesizes two previously disconnected bodies of theory to advance our understanding of how traditional phraseology makes meaning, as well as illuminate the political and social dimensions of surviving texts, through attention to Old English poets' impulse to explore subjective perspectives.